Foundations of physical activity and public health. - Kohl, Harold W., ....-; Murray, Tinker D., ....- (Champaign : Human Kinetics, 2012)
Foundations of Physical Activity and Public Health is the first textbook to define the intersection of kinesiology and public health and combine them into a clear picture of how the two fields interact. It details the planning, implementation, and evaluation of successful physical activity promotion programs.
Keywords: Gezondheidspromotie